THE ROLE OF ECONOMIC INTEGRATION FOR THE FUNCTIONING OF POLISH AGRICULTURAL SECTOR ON THE EXAMPLE OF THE RURAL DEVELOPMENT PROGRAM (RDP) - Stepień, Sebastian; Polcyn, Jan (Annales Universitatis Apulensis Series Oeconomica, 2017)
The aim of the paper is to evaluate the Rural Development Program (as a part of Common Agricultural Policy of the EU) from the point of view of impact on the agri-food sector in Poland. An introduction to the analysis is the identification of structural changes in Polish agriculture under the conditions of integration with the European Union. The following step consists in the assessment of the RDP for 2004-2006 and 2007-2013. The final stage is an evaluation of the rural support in the current financial perspective. It is clear from the considerations that the RDP first set up the multiplying effects of investment expenditure (under modernization programs), thus increasing the efficiency of the use of production factors (mainly labor and land). Income support, in the form of funds for less-favored areas (and earlier as well as supplementary payments) has become an important accelerator of innovation, modernization and structural transformation processes in the countryside. The RDP resources (including structural pensions) also served the expected transformations of the agrarian structure. Finally, part of the money was used to reduce excessive employment in the agricultural sector (diversification, micro-enterprise development). The article is an overview of the topic literature and statistical data, as well as previous studies of one of the authors. . It uses elements of descriptive analysis, meta-analysis and deductive inference.